Unemployment Benefits and Their Usefulness on Labour Outcomes: A Comparison of Nordic Welfare States - Okoli, Chisom (My University, 2024)
This study examines the effects of unemployment benefits on labour outcomes in Nordic countries. Since the welfare state has moved from mere compensation to becoming a social investment, it is important to see how an important welfare provision like unemployment benefits has affected labour outcomes in the Nordics with a sustainable welfare state being the goal. In this study, the questions asked include; are unemployment benefits associated with the probability to be employed in Nordic countries, and are unemployment benefits associated with duration of unemployment in Nordic countries? The study utilizes the Luxembourg Income Study (LIS) data with an observation of 4,485,451 individuals across the 5th to 10th wave (1995-2016). The Luxembourg Income Study (LIS) data is used to run a logistics regression model and a survival analysis test model to measure the probability of being employed in the Nordics after receiving benefits and the duration of unemployment after receiving unemployment benefits. The results from the logistic regression show that a unit increase in unemployment benefits is associated with the probability of being unemployed when other variables are controlled for. The survival analysis test shows that in the two countries (Finland and Sweden) used in the model, the country with lower levels of compensation which is Finland has a shorter duration of unemployment compared to the more generous Sweden when unemployment benefits are controlled for. The study concludes that unemployment benefits do not have a major effect on the labour outcome of employment in the Nordics but can also explain longer unemployment spells amongst those who receive benefits. The study recommended that a panel study follow up on individuals who receive unemployment benefits to better study the effect of the benefits on their labour outcomes.
Keywords: Unemployment benefits, welfare, labour, Nordic